2008
DOI: 10.1111/j.1464-0597.2008.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Facets of Job Satisfaction and Task and Contextual Performance

Abstract: This study examined the relationship between job satisfaction and task and contextual performance. Specifically, it assessed this relationship for overall as well as facets of job satisfaction. Four hundred and forty-four employees in a manufacturing plant completed measures of job satisfaction and their supervisors completed measures of task and contextual job performance. Results indicate that the relationships between overall job satisfaction and task and contextual performance were the same. However, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 67 publications
5
91
0
14
Order By: Relevance
“…This hypothesis was also accepted as it had positive and significant results. Previous research's also supported these results as interactional justice impacts employees' performance [23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 71%
“…This hypothesis was also accepted as it had positive and significant results. Previous research's also supported these results as interactional justice impacts employees' performance [23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 71%
“…In general, it can be said that this study follows the trend of the literature to identify the predictive relationship between job satisfaction and performance (Coelho Jr. & Borges-Andrade, 2011;Edwards et al, 2008;Fischer, 2003;Schleicher et al, 2004;Sy et al, 2006). In turn, the result of the obtained model faces the evidence found by Bowling (2007), who questioned the significance of the relationship between satisfaction and performance, especially when other variables were involved.…”
Section: Discussionsupporting
confidence: 48%
“…The research of Coelho Jr. (2009) demonstrated that satisfaction influences individual job performance; however, this influence depends on the unit in which the employee is allocated. In reviewing the recent literature, studies have pointed to a positive predictive relationship between job satisfaction and job performance, with emphasis in most of these studies, on the task performance (Coelho Jr. & Borges-Andrade, 2011;Edwards, Bell, Arthur Jr., & Decuir, 2008;Fischer, 2003;Schleicher, Watt, & Greguras, 2004;Sy, Tram, & O'Hara, 2006).…”
Section: Job Satisfaction As a Predictor Of Individual Performancementioning
confidence: 99%
“…The surveys including sixth five 7-scale questions(after neglecting the questions 38,43 in perfectionism measure; question 5 in job performance measure; which decreased the reliability,) after referring questionnaires from Rizzo (1970) [10] , .Hewitt, P.L., & Flett, G.L. (1990) [11] , Edwards and Rothbard (1999) [12] , Williams, L. J., & Anderson, S. E. (1991) [13] and scales for demographic variables. Cronbach's Alpha of questionnaire was 0.790.…”
Section: Methodsmentioning
confidence: 99%